Green extraction of healthy and additive free mitochondria with a conventional centrifuge - Lin, Ying-Ting; Chen, Sung-Tzu; Chang, Jui-Chih; Teoh, Ren-Jie; Liu, Chin-San; Wang, Gou-Jen (Lab on a chip, 2019)
In this research, we propose a novel centrifugal device for the massive extraction of healthy mitochondria with a centrifuge used in general laboratories within 30 minutes. The device mainly consists of two key components. One component is a microfluidic device, which is fabricated by photolithography, nickel electroforming, and polydimethylsiloxane casting, for the efficient disruption of the cell membrane. The other component is a stainless steel container, which is manufactured by computer numerical control machining, for the storage of the cell suspension. After assembly, the appropriate number of cells is pushed through the microfluidic device for cell membrane disruption by centrifugal force generated by a general laboratory centrifuge. The solution which contains cell debris and mitochondria are collected to purify the crude mitochondria via differential centrifugation. Compared with the quantity and efficiency of mitochondria isolated from the same number of cells using a conventional kit, device-extracted mitochondria show a more complete mitochondrial electron transport chain complex and a similar number of mitochondria verified by Western blot analysis of mitochondrial complexes IV and mitochondrial outer membrane protein Tom20, respectively, as well as a normal mitochondrial structure revealed by transmission electron microscopy. Moreover, the mitochondrial membrane potential of device-extracted mitochondria stained with tetramethylrhodamine ethyl ester is higher than that of kit-extracted mitochondria. Furthermore, the coculture of device-extracted mitochondria with fibroblasts revealed that fibroblasts could uptake foreign mitochondria through endocytosis without drug treatment. These results show that the proposed microfluidic device preserves mitochondrial protein structure, membrane integrity, and membrane potential within 30 minutes of extraction and is a useful tool for therapeutic mitochondrial transplantation and regenerative medicine. In this research, we propose a novel centrifugal device for the massive extraction of healthy mitochondria with a centrifuge used in general laboratories within 30 minutes.